(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
The article is devoted to the study of the main power of our Motherland, the process of upbringing of our youth in the spirit of military patriotism, which is the main pillar of our development, and the main priorities in the upbringing of Military Patriotism. At the same time, we will also introduce young people to the system of Military Patriotic education, as well as some attitudes that are hindered in the education of Military Patriotism today.